Pyloroplasty may reduce weight loss 1 year after esophagectomy. Issue 3 (20th March 2018) - Harada, K; Yoshida, N; Baba, Y; Nakamura, K; Kosumi, K; Ishimoto, T; Iwatsuki, M; Miyamoto, Y; Sakamoto, Y; Ajani, J A; Watanabe, M; Baba, H
SUMMARY: Weight loss after esophagectomy is common and is associated with unfavorable prognosis. However, the clinical features and surgical methods that influence postesophagectomy weight loss are not well characterized. This study aims to determine those features (especially the surgical methods) that may affect postoperative weight loss. We reviewed 221 esophageal cancer patients who had undergone esophagectomy at Kumamoto University Hospital (Kumamoto, Japan) between November 2012 and June 2015. Among these, we recruited 106 patients who had undergone transthoracic esophagectomy with gastric conduit reconstruction, had no cancer recurrence within 1 year, and no missing follow-up data. We tabulated the body weight changes and risk factors associated with weight loss exceeding 10% at 1-year postesophagectomy. The mean body weights at baseline and 1-year postsurgery were 60.3 kg (standard error (SE): 0.91) and 52.6 (SE: 0.91), respectively. One year postsurgery, the body weights had changed as follows: mean: −12.2%; median: −12.9%; standard deviation: 9.06; range: −36.1–18.56%; interquartile range: −10.5 to −14.0%. In the multivariate logistic regression analysis, the absence of pyloroplasty was the sole risk factor for more than 10% weight loss (OR: 3.22; 95% CI: 1.08–11.9; P = 0.036). Our data suggest that pyloroplasty with esophagectomy can overcome the post-surgical weight loss.